The effect of PEPPERMINT AND LEMONGRASS AROMATHERAPY CANDLES TO NAUSEA VOMITING IN FIRST TRIMESTER PREGNANT WOMEN - Donna Harriya Novidha; Nova Riesmi Prasticka (INTERNATIONAL JOURNAL OF NURSING AND MIDWIFERY SCIENCE (IJNMS), 2022)
According to studies conducted in Indonesia, 14.8% of all pregnancies involved women who experienced nausea and vomiting. 40–60% of multigravidas and 60–80% of primigravida report experiencing nausea and vomiting. These symptoms can worsen once every 1,000 pregnancies. In the first trimester of the Zora era in the Merangin Regency, Jambi Province in 2021, this study seeks to ascertain the effectiveness of peppermint and lemongrass aromatherapy candles in reducing nausea and vomiting in pregnant women. One Group Pretest-Posttest Design was the quasi-experimental method employed in this investigation. The statistical test that was employed was the statistical test, which was based on the research's findings. There was a connection between peppermint and lemongrass aromatherapy candles and nausea and vomiting in first-trimester pregnant women at Midwife Clinic Era Zora, according to the T test's p-value of 0.000 0.05. According to the study's findings, peppermint and lemongrass aromatherapy candles have an effect on nausea and vomiting in first-trimester pregnant women at Midwife Clinic Era Zora in 2021. This relationship was found using the paired T-test statistical test (Wilcoxon Signed Rank Test). Candles with peppermint and aromatherapy Pregnant women are advised to use lemongrass in the first trimester to lessen nausea and vomiting